Two-dimensional delocalized states in organometallic bis-acetylide networks on Ag(111). Issue 8 (7th February 2018) - Yang, Zechao; Gebhardt, Julian; Schaub, Tobias A.; Sander, Tim; Schönamsgruber, Jörg; Soni, Himadri; Görling, Andreas; Kivala, Milan; Maier, Sabine
Abstract : Scanning tunneling spectroscopy and density-functional theory reveal an unoccupied electronic state that is delocalized along the entire organometallic Ag-bis-acetylide network. Abstract : The electronic structure of surface-supported organometallic networks with Ag-bis-acetylide bonds that are intermediate products in the bottom-up synthesis of graphdiyne and graphdiyne-like networks were studied. Scanning tunneling microscopy (STM) and spectroscopy (STS) reveal a frontier, unoccupied electronic state that is delocalized along the entire organometallic network and proves the covalent nature of the Ag-bis-acetylide bonds. Density-functional theory (DFT) calculations corroborate the spatial distribution of the observed delocalized state and attribute it to band mixing of carbon and silver atoms combined with n-doping of the metal surface. The metal-bis-acetylide bonds are typical metal–organic bonds with mixed character containing covalent and strong ionic contributions. Moreover, the organometallic networks exhibit a characteristic graphene-like band structure with linear band dispersion at each K point.